International Law Issues Raised by the Transfer of Detainees by Canadian Forces in Afghanistan - Sassòli, Marco; Tougas, Marie-Louise (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
The transfer of Afghan detainees to Afghan authorities by Canadian forces raised concerns in public opinion, in Parliament, and was the object of court proceedings and other enquiries in Canada. This article aims to explore the rules of international law applicable to such transfers. The most relevant rule of international humanitarian law (IHL) applies to prisoners of war in international armed conflicts. However, the conflict in Afghanistan, it is argued, is not of an international character. The relevant provision could nevertheless apply based upon agreements between Canada and Afghanistan and upon unilateral declarations by Canada. In addition, international human rights law (IHRL) and the very extensive jurisprudence of its mechanisms of implementation on the obligations of a state transferring a person to the custody of another state where that person is likely to be tortured or treated inhumanely will be discussed, including the standard of care to be applied when there is an alleged risk of torture. While IHL contains the rules specifically designed for armed conflicts, IHRL may in this respect also clarify as lex specialis the interpretation of concepts of IHL. Finally, the conduct of Canadian leaders and members of the Canadian forces is governed by international criminal law (ICL). This article thus demonstrates how IHL, IHRL, and ICL are intimately interrelated in contemporary armed conflicts and how the jurisprudence of human rights bodies and of international criminal tribunals informs the understanding of IHL rules.